การสร้างหน่วยชั้นเซลล์เชื้อเพลิงพีอีเอ็ม - สุดารัตน์ สายยืนยงค์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
This research focused on the preparation and development of a small sizeMembrane Electrode Assembly (MEA) with an objective to scale up and fabricate astack under the optimum condition. It was found that spraying catalyst ink with catalystcontaining 0.5 mg/cm2 onto carbon cloth with water management layer, nafion content incatalyst layer 33%wt. and using nafion membrane 115 shown the highest current densityof 0.54 A/cm2 at 0.6 V for a 5 cm2 MEA. However, the performance of MEA scaled up to25 cm2 decreased approximately 24%. Nafion membrane 212 gave higher performancethan nafion membrane 115. It was also found that when using nafion membrane 212 waslaceration at high flow rate. So, 3-cell stack was fabricated by using nafion membrane115. The performances of fabricated PEM stack depended on various parameters forexample humidities of reactive and oxidized gases, gas flow rate and clamping force. Itwas found that the optimum operating condition for the stack was 200 sccm H2 withhumidity and 400 sccm O2 with humidity, clamping force of 60 lbf.in and the operatingpressure at 10 psig. This condition gave the power density and current density of 1.08W/cm2 and 0.6 A/cm2 at 1.8 V, respectively.